2005
DOI: 10.2214/ajr.184.1.01840200
|View full text |Cite
|
Sign up to set email alerts
|

The “Floating” Meniscus: MRI in Knee Trauma and Implications for Surgery

Abstract: The presence of a floating meniscus on MRI is a result of significant trauma to the knee leading to meniscal avulsion and is often associated with significant ligamentous injury. Alerting the surgeon to the presence of a meniscal avulsion facilitates appropriate surgical planning with meniscal reattachment to the tibial plateau.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 6 publications
0
16
0
2
Order By: Relevance
“…Dodds et al [5] showed its complex femoral origin with a fan-like blending of fibers without a distinct area of direct bony attachment, contested by some authors to be anterior [2] or posterior [5] to the femoral epicondyle, or even presenting connections with the popliteal tendon origin [1]. Although some authors illustrated a clear meniscal attachment [2,4,12], it may not be easily differentiated from the lateral inferior geniculate artery and vein [1], meniscocapsular ligaments [13,14], and iliotibial tract fibers [3,8]. Vincent et al showed in a cadaveric dissection study that the ALL has a close relationship to the lateral meniscus next to the junction of its anterior and middle thirds, but it was impossible to macroscopically assess a meniscal insertion [1].…”
Section: Discussionmentioning
confidence: 99%
“…Dodds et al [5] showed its complex femoral origin with a fan-like blending of fibers without a distinct area of direct bony attachment, contested by some authors to be anterior [2] or posterior [5] to the femoral epicondyle, or even presenting connections with the popliteal tendon origin [1]. Although some authors illustrated a clear meniscal attachment [2,4,12], it may not be easily differentiated from the lateral inferior geniculate artery and vein [1], meniscocapsular ligaments [13,14], and iliotibial tract fibers [3,8]. Vincent et al showed in a cadaveric dissection study that the ALL has a close relationship to the lateral meniscus next to the junction of its anterior and middle thirds, but it was impossible to macroscopically assess a meniscal insertion [1].…”
Section: Discussionmentioning
confidence: 99%
“…In one study [11], the presence of fluid signal intensity completely surrounding one or both horns of either meniscus suggested meniscal avulsion, especially with a fluid signal intensity thicker than 2-3 mm in the craniocaudal dimension beneath the meniscal surface. The largest fluid-filled gap measured beneath the PHMM here was 2.23 mm (mean size 1.34 mm).…”
Section: Discussionmentioning
confidence: 97%
“…The distance of mediolateral meniscal movement was calculated as the absolute value of extrusion minus the value of intrusion for each meniscus. In the sagittal images, any fluid-filled gap overlying the meniscal inferior or superior surface entirely was considered meniscal floating [11]. A meniscal flounce was defined as a folding of the free edge of the meniscus [12] on the sagittal 2D FSE T2-weighted image and was evaluated and agreed upon by two radiologists with 6 and 15 years of experience in musculoskeletal MRI.…”
Section: Position-related Changes In the Meniscimentioning
confidence: 99%
“…Beyin ve santral sinir sistemi hastalıkları: 18 Sporcu yaralanmaları 19 Menisküs teşhisi 20 Bel fıtığı teşhisi 21 Nörolojik rahatsızlıklar 22 TME rahatsızlıkları 23 Epilepsi vb.…”
Section: Manyeti̇k Rezonans Görüntüleme Nedi̇r?unclassified